The Next Wave of Suptech Innovation : Suptech Solutions for Market Conduct Supervision - World Bank (World Bank, Washington, DC, 2021)
Around the world, financial sector supervisors are experiencing a profound shift to data-driven supervision enabled by the next wave of technology and data solutions. While technology and data are not new to financial oversight, their specific application to financial consumer protection and market conduct supervision has become more widespread and sophisticated in recent years. Expanding on the World Bank’s 2018 note on supervisory technology, or suptech, this technical note catalogues a range of specific solutions that financial authorities are deploying to help increase the efficiency and effectiveness of market conduct supervision. The note identifies four categories of suptech solutions (regulatory reporting, collection and processing of complaints data, non-traditional market monitoring, document and business analysis) and provides concrete examples of 18 different suptech solutions for market conduct supervision, drawing from the experiences of 14 financial sector authorities worldwide. The note also discusses implementation considerations and enablers of successful suptech adoption commonly experienced across countries.